PERAN PENDIDIKAN PESANTREN DALAM PEMBENTUKAN KARAKTER SANTRI - Salsabil Darma Ma’arif; Nur Hasan; Dzulfikar Rodafi (VICRATINA, 2021)
In this globalization or digital era, the existence of Islamic boarding schools is needed to realize the goals of national education that have not been maximally achieved by formal educational institutions. Schools as formal educational institutions are indeed able to supervise the activities of students during the teaching and learning process, but not with their association in social life. Activities that cannot be controlled by formal educational institutions include the use of gadgets, social media and the internet when students return to their family and community. Freedom to access unlimited information has a negative impact on changing mindsets, shifting cultural values, and eroding the nation's character. Riyadlul Qur'an Islamic boarding school which is located in Ngasem Village, Ngajum District, Malang Regency is a boarding school that is increasingly trusted by the community to educate and instill character education in their children. This is the background of the researchers conducting qualitative research with the methods of observation, interviews, distributing questionnaires and document studies to explore the forms, processes and constraints of character education in the pesantren. The resultsof this study indicate that the form of the educational character of PP Riyadlul Qur'an is a boarding school that combines salaf and modern education. The process of planting character education in this cottage is carried out completely and thoroughly through 5 aspects of educational activities. Several obstacles were also found in the cottage, including the number of educators and educational infrastructure, the participation of parents and individual students. However , these obstacles can be overcome because this institution develops the nature of simplicity and openness in cooperating and involving all stakeholders and always trying to improve its educational services . Keywords: Islamic Boarding School Education, Character, Santri